Persepsi Siswa Madrasah Tsanawiyah terhadap Internalisasi Nilai-Nilai Islam melalui Pembelajaran PAI Berbasis Kearifan Lokal: Studi Survei di MTs. Irsyadul Ibad Simpang Kubu Kandang Kecamatan Pemayung - Nurul Huda (Jurnal Miftahul Ilmi: Jurnal Pendidikan Agama Islam, 2026)
This study examines how madrasah students perceive the meaningfulness of Islamic Religious Education (Pendidikan Agama Islam/PAI) integrated with local wisdom as a means of instilling Islamic values. The Malay community in Pemayung District, Batanghari Regency, Jambi, inherits a rich array of traditions deeply rooted in Islamic values, including zikir ratib, hadrah, berzanji, and patitih. However, the extent to which such local wisdom integration in formal PAI instruction is perceived as meaningful by students has never been empirically measured. This descriptive-comparative survey study involved 82 students of MTs. Irsyadul Ibad, selected through a total sampling technique. The instrument employed was the SPIN-KL Scale (40 items, α = 0.884), measuring eight perceptual dimensions on a 5-point Likert scale. Analysis results revealed an overall mean perception score of 4.12 (SD = 0.42; positive category; 82.7% positive responses). The dimension of PAI content relevance to local wisdom obtained the highest score (M = 4.24; very positive), while the dimension of Islamic identity consolidation through local culture recorded the lowest score, though still remaining positive (M = 3.98). Independent samples t-tests indicated a significant difference based on students' active participation in religious study circles (pengajian) (t(80) = 4.74, p < 0.001, d = 1.07), whereas gender and grade level yielded no significant differences. These findings underscore the importance of collaboration between madrasah institutions and religious-cultural communities in strengthening the internalization of Islamic values.